2017
DOI: 10.4025/actasciagron.v39i4.32952
|View full text |Cite
|
Sign up to set email alerts
|

<b>Salinity reduces carbon assimilation and the harvest index of cassava plants (<i>Manihot esculenta</i> Crantz)

Abstract: ABSTRACT. This study was developed to evaluate the effects of salinity on the growth and gas exchange of cassava plants, cultivar Verdinha. The four concentrations of NaCl (mM) were as follows: 0, 20, 40, and 60. Under salinity, the lowest concentration of Na + ions was observed in the tuberous roots; however, the dry matter of tuberous roots was reduced with an application of just 20 mM NaCl. The harvest index was reduced 50% with the highest salt concentration. Salinity reduced carbon assimilation (A), stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
0
19
1
5
Order By: Relevance
“…According to Muuns and Tester (2008), excess salt reduces the development of the plant due to osmotic effects, which hinder the absorption and transport of water in soil-plant systems; these phenomena occur in addition to the energy costs of osmotic and biochemical adjustment mechanisms, which are necessary for the survival of plants under stress. The gradual increase in the DMS/DMR ratio with increasing irrigation water salinity ( Figure 2D) conflicts with the results of several studies carried out under controlled conditions or in field conditions, in which it is accepted by most authors that the aerial parts of the plants are usually more sensitive to salt stress (Cruz, Coelho Filho, Coelho, & Santos, 2017). Conversely, a greater reduction in the root growth of plants exposed to salinity stress was also observed in the sorghum genotype CSF 20 (Sousa et al, 2010) and in rice (Rodrigues et al, 2005), and it is possible to suggest that the mechanisms of acclimatization to stress differ between species and possibly depend on the growth conditions.…”
Section: Growth Analysiscontrasting
confidence: 83%
See 1 more Smart Citation
“…According to Muuns and Tester (2008), excess salt reduces the development of the plant due to osmotic effects, which hinder the absorption and transport of water in soil-plant systems; these phenomena occur in addition to the energy costs of osmotic and biochemical adjustment mechanisms, which are necessary for the survival of plants under stress. The gradual increase in the DMS/DMR ratio with increasing irrigation water salinity ( Figure 2D) conflicts with the results of several studies carried out under controlled conditions or in field conditions, in which it is accepted by most authors that the aerial parts of the plants are usually more sensitive to salt stress (Cruz, Coelho Filho, Coelho, & Santos, 2017). Conversely, a greater reduction in the root growth of plants exposed to salinity stress was also observed in the sorghum genotype CSF 20 (Sousa et al, 2010) and in rice (Rodrigues et al, 2005), and it is possible to suggest that the mechanisms of acclimatization to stress differ between species and possibly depend on the growth conditions.…”
Section: Growth Analysiscontrasting
confidence: 83%
“…Aquino et al (2007) also reported a decrease in the photosynthetic vari ables in sorghum plants after 40 days of salinity stress. Several other plant species, including jatropha (Silva, Ribeiro, Ferreira-Silva, Viégas, & Silveira, 2011), citrus (Lopéz-Climent, Arbona, Peréz-Clemente, & Goméz-Cadenas, 2008), cowpea (Assis Junior et al, 2007) and cassava (Cruz et al, 2017), have shown limitations of these variables as a function of increased salinity. In addition to the decrease in the photosynthetic rate, the reduction in leaf area ( Figure 1B) caused by increasing salinity levels considerably decreased the area destined for photosynthesis, which in turn reduced the production capacity of the genotype (Munns & Tester, 2008).…”
Section: Leaf Gas Exchange and Relative Chlorophyll Contentmentioning
confidence: 99%
“…Kham Pom also had higher soil salinity in the subsoil than the other environments (data not shown), with an appearance of salt on the top of the soil surface during the dry period within 90 DAP, which can potentially increase crop stress and reduce cassava growth and final storage root yield. A previous study reported that low total N and exchangeable K limited the storage root yield (Aina et al, 2007), whereas Cruz et al (2017) found that soil salinity reduced both total dry weight and storage root dry weight of cassava. The significance in interactions between genotype and environment for almost all cassava traits demonstrated different responses of the cassava genotypes for each environment, except for LGR during 120 to 180 DAP.…”
Section: Discussionmentioning
confidence: 92%
“…By analyzing melons physiologically, it was verified that a soil salinity of up to 1.02 dS m -1 promoted an increase in the net CO 2 assimilation (6.79 μmol m -2 s -1 ), decreasing gradually from this plant saline level ( Figure 3A). Probably, this reduction is related to photochemical damage, such as photoinhibition or photooxidation, or biochemical fixation of carbon under saline stress, thus interfering negatively in the plant development (Bosco et al 2009, Cruz et al 2017. Similar results were found by Melo et al (2017), which showed decreases in gas exchange from 1 dS m -1 .…”
Section: Resultsmentioning
confidence: 61%
“…Regarding salinity, under stress conditions, the inhibition of the electron transport used in photosynthesis and the enzyme activity of the Calvin cycle is observed (Esteves & Suzuki 2008). Therefore, the reduction of photosynthesis leads to a decrease in yield, since the production index may reduce up to 50 % under salinity conditions (Cruz et al 2017).…”
Section: Palavras-chavementioning
confidence: 99%